Penatalaksanaan Deep Bite Menggunakan Peranti Lepasan (Laporan Kasus) - Putu Ika Anggaraeni (School of Dentistry Faculty of Medicine Udayana University, 2021)
Background: Deep bite is a condition when there is an excess vertical overlap between the maxillary and mandibular anterior teeth. A simple deep bite is limited to the dentition and its alveolar process. Untreated deep bite tends to increase anterior crowding, maxillary incisors protrusion, and also generate periodontal and temporomandibular problems. This serial case report aims to describe the management of deep bite using removable appliances in Udayana University Hospital. Case report: Two deep bite cases with overbite more than one-third of clinical crown height mandibular incisors. Both cases were treated using a sved bite plate and maxillary inclined bite plate. Deep bite in both cases was corrected after 3-4 months of treatment using the bite plate. Conclusion: Anterior bite plate can be effective in the management of dental deep bites. Latar belakang: Deep bite merupakan suatu kondisi vertical overlapping yang berlebihan gigi insisivus maksila terhadap gigi insisivus mandibula pada oklusi sentrik, yakni lebih besar dari 30% atau 1/3 panjang mahkota klinis insisivus mandibular. Faktor dental penyebab deep bite hanya melibatkan gigi-gigi dan tulang alveolarnya, Deep bite yang tidak dirawat cenderung akan memperparah kondisi crowding anterior, protrusi, masalah periodontal dan temporomandibula. Laporan kasus ini bertujuan untuk memaparkan penatalaksanaan kasus deep bite menggunakan peranti lepasan di RS Universitas Udayana. Laporan Kasus: Dua orang pasien dengan kasus deep bite memiliki tampilan klinis gigi insisivus maksila menutupi lebih dari 1/3 tinggi mahkota klinis gigi insisivus mandibula. Kedua kasus tersebut dirawat dengan menggunakan sved bite plate dan maxillary inclined bite plate, dimana pemakaian selama 3-4 bulan memperlihatkan deep bite terkoreksi. Simpulan: Peranti lepasan berupa bite plate anterior dapat berfungsi secara efektif dalam penatalaksanaan kasus deep bite yang disebabkan oleh faktor dental.